2009
DOI: 10.1002/ibd.20843
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after admission for acute severe ulcerative colitis in Oxford: The 1992–1993 cohort

Abstract: One week after admission with ASC in the prebiologic era, IRs had a 50% chance of colectomy within a year and 70% within 5 years, despite cyclosporin and azathioprine where appropriate. The maximum duration of remission in CRs was almost 5 times longer than IRs. It is unknown whether biologics change the long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 19 publications
4
60
1
Order By: Relevance
“…The colectomy rate at admission in our study was lower than that reported in the West, but matched the Asian data ( Table 3 ). The longterm colectomy rate in our study was 34%, which was lower than that reported by two earlier studies from Sweden (64%) [72] and Oxford (61%) [73] , but comparable to the recent studies from Oxford (40%) [70] , Hungary (25%) [74] , and South Korea (29%) [75] . These differences could be explained by an absence of immunomodulator use in the Swedish cohort, regional differences in the behaviour of disease (Asia vs. West), and the duration of follow-up.…”
Section: Long-term Disease Course and Treatmentcontrasting
confidence: 55%
“…The colectomy rate at admission in our study was lower than that reported in the West, but matched the Asian data ( Table 3 ). The longterm colectomy rate in our study was 34%, which was lower than that reported by two earlier studies from Sweden (64%) [72] and Oxford (61%) [73] , but comparable to the recent studies from Oxford (40%) [70] , Hungary (25%) [74] , and South Korea (29%) [75] . These differences could be explained by an absence of immunomodulator use in the Swedish cohort, regional differences in the behaviour of disease (Asia vs. West), and the duration of follow-up.…”
Section: Long-term Disease Course and Treatmentcontrasting
confidence: 55%
“…The risk of the development of these complications is much lower in UC than in CD. In addition, the colectomy rate of acute severe UC is reported to be significantly lower in Korean patients [55] than in British patients [56,57] : 16.2 versus 29.4% during index hospitalization and 15.7 versus 50% during a median 10-year follow-up after discharge. Therefore, the strategy of discontinuing anti-TNF therapy after a certain period of remission and later reintroducing it on an on-demand basis may be worth evaluating in Asian patients with UC.…”
Section: Combination Therapy Versus Monotherapymentioning
confidence: 99%
“…Serological markers able to predict an aggressive course are antiglycan antibodies and antibacterial antibodies [2]. In UC, clinical, genetic and serological risk factors for more aggressive disease are extensive colitis, sclerosing cholangitis, the presence of extraintestinal manifestations, a young age, a nonsmoking status, systemic inflammation, no response to first-line therapy, no mucosal healing 1 year after diagnosis, HLA variants and antineutrophil cytoplasmic antibodies [11,12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%